Consumer Legal Protection on the Right to Refund in Paid Digital Applications - Wardah, Siti Syarifah Wafiqah; Syarifuddin, Syarifuddin (Universitas Negeri Makassar, 2025)
The development of subscription-based paid digital application services such as Netflix, Spotify, and YouTube Premium has changed people's consumption patterns, but has raised legal issues related to refund rights due to service failures, unilateral cancellations, or system errors. This study analyzes consumer refund regulations in Indonesia, the obstacles to their implementation, and formulates an ideal protection model through a normative approach with legislative, conceptual, and comparative analysis. The results show that refund regulations in Indonesia are still general (Consumer Protection Law, Electronic Information and Transaction Law, Government Regulation No. 80/2019) and not specific to paid digital services, with obstacles including slow refund processes, disadvantageous standard clauses, and low consumer literacy. A comparison with the European Union, the United States, and Singapore confirms the need for a cooling-off period, a chargeback mechanism, and contextual regulations. This study affirms refunds as a basic consumer right by Nasution, part of distributive justice by Rawls, and requires the regulation of standard clauses in digital contracts. In practical terms, this study provides input for regulators such as the Financial Services Authority and the Ministry of Communication and Information Technology, business actors, and consumers in strengthening justice and trust in the digital ecosystem.